Etika Tabligh Perspektif Muballigh - Mualifah, Ulfah (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
This study aims to analyze the ethics of tabligh (Islamic preaching) among muballigh in the Greater Bandung area, focusing on moral values, professionalism, and social responsibility in delivering Islamic messages. Using a descriptive qualitative approach, in-depth interviews were conducted with active muballigh such as Tata Sukayat, Abdul Mujib, Mukhlis Aliyudin, and Tantan Taqyudin. The findings reveal three main dimensions of tabligh ethics: (1) ethical message delivery, emphasizing honesty, gentleness, and wisdom; (2) personal ethics of the muballigh, reflecting sincerity, exemplary behavior, and noble character; and (3) social and media ethics, which require responsibility for public impact and sensitivity to digital contexts. The study proposes a conceptual model called Integrative Tabligh Ethics, which unites spiritual, social, and professional values in Islamic preaching. The implications highlight the need for continuous ethical training and the establishment of a professional code of ethics for muballigh, ensuring that tabligh serves as a means of spreading Islam as a rahmatan lil ‘alamin (mercy to all creation).